Ontology directed semantic annotation process - Kuptabut, Suthasinee; Netisopakul, Ponrudee (My University, 2010)
This paper proposes a process for annotating semantic concepts to sentences excerpted from webpages. The annotation process is guided by a domain specific ontology and an entities knowledge base. The overall process has four steps: extracting textual contents from a webpage, selecting relevant sentences, extracting clauses and phrases from a sentence and assigning concepts to phrases. The process is demonstrated using weather news webpages.
Keywords: Component; Knowledge base; Ontology; Semantic analysis; Semantic annotation